Hydrogen sulfide upregulates renal AQP‐2 protein expression and promotes urine concentration. Issue 1 (23rd July 2018) - Luo, Renfei; Hu, Shan; Liu, Qiaojuan; Han, Mengke; Wang, Feifei; Qiu, Miaojuan; Li, Suchun; Li, Xiaosa; Yang, Tianxin; Fu, Xiaodong; Wang, Weidong; Li, Chunling
ABSTRACT: Increasing evidence supports the important role of H2 S in renal physiology and the pathogenesis of kidney injury. Whether H2 S regulates water metabolism in the kidney and the potential mechanism are still unknown. The present study was conducted to determine the role of H2 S in urine concentration. Inhibition of both cystathionine‐γ‐lyase (CSE) and cystathionine‐β‐synthase (CBS), 2 major enzymes for endogenous H2 S production, with propargylglycine (PPG) and amino‐oxyacetate (AOAA), respectively, caused increased urine output and reduced urine osmolality in mice that was associated with decreased expression of aquaporin (AQP)‐2 in the renal inner medulla. Mice treated with both PPG and AOAA developed a urine concentration defect in response to dehydration that was accompanied by reduced AQP‐2 protein expression. Inhibition of CSE alone was associated with a mild decrease in AQP‐2 protein level in the renal medulla of heterozygous CBS mice. GYY4137, a slow H2 S donor, markedly improved urine concentration and prevented the down‐regulation of renal AQP‐2 protein expression in mice with lithium‐induced nephrogenic diabetes insipidus (NDI). GYY4137 significantly increased cAMP levels in cell lysates prepared from inner medullary collecting duct (IMCD) suspensions. AQP‐2 protein expression was also upregulated, but was significantly inhibited by the adenyl cyclase inhibitor MDL12330A or the PKA inhibitor H89, but not the vasopressin 2 receptor (V2 R) antagonist tolvaptan. Inhibition of endogenous H2 S production impaired urine concentration in mice, whereas an exogenous H2 S donor improved urine concentration in lithium‐induced NDI by increasing AQP‐2 expression in the collecting duct principal cells. H2 S upregulated AQP‐2 protein expression, probably via the cAMP‐PKA pathway.—Luo, R., Hu, S., Liu, Q., Han, M., Wang, F., Qiu, M., Li, S., Li, X., Yang, T., Fu, X., Wang, W., Li, C. Hydrogen sulfide upregulates renal AQP‐2 protein expression and promotes urine concentration. FASEB J. 33, 469–483 (2019). www.fasebj.org